The pigeon needs a bath! - Willems, Mo (New York : Hyperion Books for Children, an imprint of Disney Book Group, 2014)
"The Pigeon is dirty and he needs a bath, but he won't go willingly"--
Keywords: Baths -- Fiction; Pigeons -- Fiction; Baths -- Juvenile fiction; Pigeons -- Juvenile fiction; Baths; Pigeons; Fiction; Juvenile works